Adaptive detached eddy simulation of transition under the influence of free-stream turbulence and pressure gradient. (29th March 2021) - Yin, Zifei; Ge, Xuan; Durbin, Paul
Abstract: Abstract : The basic question of whether a hybrid method for turbulence simulation can plausibly capture laminar-to-turbulent transition is addressed. The ^2 – ω adaptive detached eddy simulation model (Yin & Durbin, Intl J. Heat Fluid Flow, vol. 62, 2016, pp. 499–509) does so. It dynamically adjusts a model constant, based on local mesh resolution and instantaneous flow features. In a laminar flow, the adaptive procedure returns zero subgrid viscosity, and large-scale low-frequency perturbations are resolved on the grid. However, rather than fully simulating transition, the hybrid model switches on at transition; small-scale turbulence is not resolved. It is found that the correct transitional behaviour is captured because the adaptive formulation responds to the initiation of small-scale components in the field of velocity gradient. The current work addresses flat-plate transition under the influence of free-stream turbulence and pressure gradient, encompassing bypass and separation-induced transition. First, the transition prediction mechanism of the adaptive model is explained. Then, the ability to predict transition statistically is evaluated, along with sensitivity studies of boundary conditions and mesh resolution.